Planos diretores participativos e gestão urbana em cidades médias sob o estatuto da cidade - Terci, Eliana Tadeu; Otero, Estevam Vanale; Goulart, Jefferson Oliveira [UNESP] (My University, 2014)
The paper analyzes the implementation of the new regulatory framework of urban policy in Brazil, synthesized by the Constitution of 1988 and its subsequent regulations by the Statute of the City (Federal Law No. 10.257/2001). The empirical analysis focuses on three medium-sized cities in the state of São Paulo (Piracicaba, Bauru and Rio Claro), and addresses three complementary dimensions. First: interprets the participatory processes that resulted in the new Master Plan. Second, analyzes the crisis of the developmental model for understanding the transformations experienced by the Brazilian urban network, through which the medium-sized cities took on increasing economic relevance. Third: examines the inclusion and regulation of Special Zones of Social Interest (ZEIS) and how this instrument has been used in dealing with urban problems and the housing deficit. Apart from normative considerations, the study aims to assess the actual contribution of the City Statute in the democratization of urban management.

El artículo analiza la aplicación del nuevo marco regulador de la política urbana brasileña, sintetizado por la Constitución de 1988 y su posterior reglamentación por el Estatuto de la Ciudad (Ley Federal No. 10.257/2001). El análisis empírico se centra en tres ciudades intermedias del estado de São Paulo (Piracicaba, Bauru y Rio Claro), en tres dimensiones complementarias. Primera: interpreta los procesos participativos que resultaran en los nuevos Planes de Ordenación Urbana. Segunda: analiza la crisis del modelo desarrollista para la comprensión de las transformaciones en la red urbana brasileña, con creciente relevancia económica de las ciudades intermedias. Tercera: examina la reglamentación de las Zonas Especiales de Interés Social (ZEIS) y como este instrumento ha sido utilizado para enfrentar los problemas urbanos y la escasez de vivienda. Además de las consideraciones normativas, se busca evaluar la efectiva contribución del Estatuto de la Ciudad en la democratización de la gestión urbana.

O trabalho analisa a implantação do novo marco regulatório da politica urbana brasileira, sintetizado pela Constituição Federal de 1988 e sua posterior regulamentação através do Estatuto da Cidade (Lei Federal nº 10.257/2001). A análise empírica se concentra em três cidades médias do interior do estado de São Paulo (Piracicaba, Bauru e Rio Claro), e aborda três dimensões complementares. Primeira: interpreta os processos participativos que resultaram nos novos Planos Diretores. Segunda: analisa a crise do modelo desenvolvimentista para compreender as transformações experimentadas pela rede urbana brasileira, através dos quais as cidades de porte médio assumiram crescente relevância econômica. Terceira: examina a inclusão e regulamentação das Zonas Especiais de Interesse Social (ZEIS) e como este instrumento vem sendo utilizado no enfrentamento do passivo urbano e do déficit habitacional. Para além de considerações normativas, o estudo pretende avaliar a efetiva contribuição do Estatuto da Cidade na democratização da gestão urbana.
Participative master plans and urban management in medium-sized cities under the statute of the city
Planes de ordenación urbana participativos y gestión urbana en ciudades intermedias bajo el estatuto de la ciudad
Keywords: Statute of the city; Participative master plans; Urban management; ZEIS; Estatuto de la ciudad; Planes de ordenación urbana participativos; Gestión urbana; ZEIS; Estatuto da cidade; Planos diretores participativos; Gestão urbana; ZEIS